Blue infrastructure as nature-based solutions for urban sustainability: Evaluating local perceptions from four Indian megacities - Koushik Chowdhury; Sukanya Basu; Malay Pramanik; Tobias Plieninger (Nature-Based Solutions)
Urban blue infrastructure provides multiple economic, social, and ecological benefits to local residents, and can enhance urban sustainability. However, few studies have examined the potential of traditional forms of blue infrastructure as nature-based solutions for mitigating common challenges of urban sustainability. The perceptions of 616 urban dwellers from four Indian megacities were analyzed through surveys to understand and demonstrate how blue infrastructure can be seen as a nature-based solution to urban sustainability challenges. A quantitative methodology involving descriptive statistics, Spearman correlations, and binary logistic regression was used to analyze survey data. Results showed that blue infrastructure provides multiple ecosystem services to the urban residents, with regulating and cultural services being most prominently valued. Both neglected and well-maintained blue infrastructure demonstrated significant potential as nature-based solutions for improving urban sustainability, but they contribute differently. The socio-cultural characteristics of the respondents significantly influenced their perceptions of the significance of blue infrastructure in addressing urban sustainability challenges.